Controlled photorelease of alkynoic acids and their decarboxylative deprotection for copper-catalyzed azide/alkyne cycloaddition - Vohradská, Nikoleta; Sánchez-Carnerero, Esther M; Pastierik, Tomáš; Mazal, Ctibor; Klán, Petr (Chemical communications (Cambridge, England), 2018)
A controlled photorelease of alkynoic acids from the meso-methyl BODIPY photoremovable protecting group facilitates their subsequent efficient decarboxylation to give terminal alkynes for a CuI-catalyzed azide/alkyne cycloaddition. The quantum efficiencies of the photochemical step and the kinetics of the click reaction step are reported.